The fury [large type] - Michaelides, Alex, 1977- (Thorndike Press large print top shelf., 2024)
"This is a tale of murder. Or maybe that's not quite true. At its heart, it's a love story, isn't it? Lana Farrar is one of the most famous women in the world. Every year, she invites her closest friends to her private Greek island. You may think you know this story. It had all the necessary ingredients for a press sensation: a celebrity, a private island, and a murder. We found ourselves trapped there overnight. What followed was a game of cat and mouse--a battle of wits building to an unforgettable climax. The night ended in violence and death, as one of us was found murdered. My name is Elliot Chase, and I'm going to tell you a story unlike any you've ever heard"--